. Kronecker Solutions fort he Matrix Differantial Equations - Gençoğlu, M.tuncay (My University, 2015)
In this paper, the linear matrix differantial equations which is a special case of matrix differantial equations has been formulated by the consepts of of the matrix differantial equations and Kronecker products and investigated by the Kronecker products. The formulation of the matrix differantial equation obtained by use of the linear matrix equations and Kronecker products have been applied to the matrix differantial equations and some important results have been found. It is shown that in solutions of the equation and its reduced case have emerged the importance of generalized inverse matrix and matrix functions.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Matrix functions Kronecker products Matrix differantial equations